IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS AI CANVA TERHADAP KEMAMPUAN KOGNITIF ANAK USIA DINI KELOMPOK A DI TK AL-MUHAJIRIN - Lulu Nadiyah; Irfan Fauzi Rahmat; Andi Ali Kisai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an interactive learning medium based on AI Canva to improve the cognitive ability of group A early childhood students at TK Al-Muhajirin, Peusing Village, Jalaksana District, Kuningan Regency. This research is a research and development (R&D) study using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were group A students, consisting of an individual trial with three children and a small-group trial with ten children, along with a material expert, a media expert, and the classroom teacher as validators. Data were collected through expert validation questionnaires, child response observation sheets, and semi-structured interviews, then analyzed descriptively using quantitative and qualitative approaches. The results show that the AI Canva-based learning media obtained a mean score of 2.57 (good category) from the material expert, 3.64 (very good category) from the media expert, and a response percentage of 87.69% (very good category) from the group A trial. The implementation of the media also indicated an improvement in children's cognitive ability in learning and problem-solving, logical thinking, and symbolic thinking. These findings indicate that AI Canva-based learning media is valid, practical, and effective for stimulating the cognitive development of early childhood group A students.